Randomized and double-blinded controlled trial: percutaneous trigger finger release concomitant steroid injection versus percutaneous trigger finger release alone - Jaroenporn, Woraphon; Nitiwarangkul, Lertkong; Rattanavarinchai, Jirantanin; Tangmanasakul, Akegapon; Wangrattanapranee, Thanapol; Pituckanotai, Kwanchai (International Journal of Research in Orthopaedics, 2025)
Background: Corticosteroid injection is a common nonoperative treatment that provides immediate pain relief but carries a risk of recurrence. Percutaneous A1 pulley release is a minimally invasive alternative to open surgery, offering comparable outcomes. However, postoperative pain remains a concern. This study evaluated the effect of combining corticosteroid injection with percutaneous A1 pulley release on postoperative pain control compared to percutaneous release alone. Objective was to compare early postoperative pain control, quality of life, and complications between percutaneous A1 pulley release alone and with corticosteroid injection. Methods: This was a randomized, double-blinded controlled trial including 76 patients diagnosed with trigger finger. Participants were randomly assigned to group A (percutaneous A1 pulley release with corticosteroid injection, n=36) or group B (percutaneous A1 pulley release alone, n=40). Primary outcome measures included postoperative pain scores (visual analog scale, VAS), while secondary outcomes assessed quality of life (quick disabilities of the arm, shoulder, and hand score, qDASH), patient satisfaction, and complications. Results: A total of 76 patients were enrolled, with no significant differences in baseline characteristics between groups. Pain scores (VAS) decreased in both groups from day 1 to day 3 (group A: 5.33 to 4.11; group B: 6.90 to 5.00, p>0.05). However, group A exhibited significantly lower pain scores from postoperative day 4 to 6 (1.78 versus 4.00, p<0.05), a trend that persisted through weeks 1 and 2, as well as at 1 and 2 months postoperatively. Quality of life (qDASH) and patient satisfaction were slightly higher in group A, but differences were not statistically significant (p>0.05). No major complications (e.g., infection, nerve injury, tendon rupture, recurrent triggering, or bowstringing) were reported in either group. Conclusions: The addition of corticosteroid injection to percutaneous A1 pulley release significantly improves early postoperative pain control without affecting functional recovery or patient satisfaction. These findings support the safety and efficacy of corticosteroid injection in reducing postoperative discomfort. Future studies should explore long-term outcomes, recurrence rates, and return-to-work effects.